The effects of cutting speed and change in cutting tool materials on surface roughness in bone-cutting procedures - Sawangsri, Worapong; Addepalli, Phanindra; Saiful Anwar, Che Ghani (International OCSCO World Press, 2024)
Purpose Surface roughness is a reliable indicator of bone cell damage in bone-cutting processes. This novel study investigates the effects of spindle speed, feed rate, and cutting tool materials on milling artificial bone specimens.